Selection of an optimal supplier - Ćosić, Predrag, inženjer strojarstva (Array, 2020)
The paper describes the selection of an optimal supplier from China based on three obtained bids to produce 120,000 forged pieces, which is the primary process for shaft production. The choice was made using the AHP method based on the Expert Choice software program and Multiple-Criteria Decision-Making (MCDM). The key information when choosing the optimal supplier of large number of forgings is to define the objective of the task, decision tree with weighted criteria and sub-criteria, consistency checking and possible reconsideration using brain storming when defining the strength of criteria/sub-criteria. To some extent, this may reduce initial subjectivity in the decision-making process in the Decision Support System.